STRATEGI PEMERINTAH KOTA SUKABUMI DALAM MENJAGA STABILITAS HARGA PANGAN POKOK - Sani, Faisal; Sampurna, Rizki Hegia; FY Basori, Yana Fajar (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
Food price fluctuations and inflation in Sukabumi City are triggered by limited land and reliance on external supplies. Responding to this phenomenon, the local government's stabilization strategy is examined qualitatively using the Strategy Change Cycle framework. Analytical findings reveal that market interventions like the Cheap Food Movement and Subsidized Market Operations coordinated by TPID effectively dampen short-term price spikes. However, the implemented strategies remain reactive, constrained by budget capacities, and fail to address structural root problems. Therefore, the direction of local policies must shift toward a preventive approach by strengthening regional food reserves and developing local commodities to achieve sustainable food independence.